2018
DOI: 10.6007/ijarped/v7-i3/4429
|View full text |Cite
|
Sign up to set email alerts
|

Are Biology Pre-service Teachers ready to Implement 21st Century Skill in Teaching and Learning in Nigeria?

Abstract: The 21 st century skills are important aspect of education in our present age. Numerous benefits of incorporating skill such as Information and Communication Technology (ICT) in education have been unearthed, therefore, ICT should be widely used in teaching and learning (TnL) processes. However, in order to use this skill in teaching, teachers have to possess certain level of readiness in terms of confidence; awareness and motivation; perception, training; knowledge and equipment. In relation to that, this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…For serving teachers, the results of some studies (Ameen et al, 2019;Chege, 2014;Rahimi & Yodallahi, 2010) showed no gender difference in their readiness to use ICT to teach. Results of some other studies (Bakar & Mohammed, 2008;Francisca & Samsudin, 2018;Morreale et al, 2015) showed no significant gender difference in the readiness of pre-service teachers to use ICT to teach. However, studies of Badri et al (2014), Lee et al (2009), andSummak et al (2010) found significant gender difference in the readiness of serving teachers to use ICT to teach their subjects.…”
Section: Differences On the Extent Of Pre-service Teachers Readiness ...mentioning
confidence: 83%
“…For serving teachers, the results of some studies (Ameen et al, 2019;Chege, 2014;Rahimi & Yodallahi, 2010) showed no gender difference in their readiness to use ICT to teach. Results of some other studies (Bakar & Mohammed, 2008;Francisca & Samsudin, 2018;Morreale et al, 2015) showed no significant gender difference in the readiness of pre-service teachers to use ICT to teach. However, studies of Badri et al (2014), Lee et al (2009), andSummak et al (2010) found significant gender difference in the readiness of serving teachers to use ICT to teach their subjects.…”
Section: Differences On the Extent Of Pre-service Teachers Readiness ...mentioning
confidence: 83%
“…A questionnaire, adapted from those used in similar studies, such as [69] (Ghana), [27] (Nigeria), and [26] (Slovenia), was used to collect data intended to answer the research question. It consisted of closed-ended items measured on a five-point Likert scale with the alternatives "1 = never used (not at all)", "2 = very irregularly used (at least once a term)", "3 = irregularly used (at least once a month)", "4 = regularly used (at least once a week)", and "5 = very regularly used (almost daily)".…”
Section: Methodsmentioning
confidence: 99%
“…This is probably because ICT affords quality instruction that complies with constructivism [24]. Few empirical studies [25]- [27] have confirmed that ICTs bolster efforts to better the quality of pedagogy implemented in classrooms; actually, they believe that, use of ICTs in classrooms would ensure academic excellence in instruction. Thus, countries with disparate economic positions encourage the use of contemporary technologies as instructional instruments in different subjects [28].…”
Section: Information and Communication Technology Practices Inmentioning
confidence: 99%
“…Pendidikan sains-termasuk biologi-untuk peserta didik berada pada posisi penting, karena mereka dihadapkan dengan tantangan ilmiah yang sangat besar yang harus mereka hadapi saat ini (Anderman & Sinatra, 2009;Chen & Huang, 2017). Oleh karena itu, guru harus siap dan mampu mengimplementasikan aspek keterampilan abad ke-21 dalam kegiatan belajar mengajar biologi (Francisca & Samsudin, 2018;Haviz, Karomah, Delfita, Umar, & Maris, 2018;Yanti, Maridi, & Sutarno, 2019).…”
Section: Pendahuluanunclassified